The Board of Peace and the Illusion of Palestinian Liberation: Stabilization, Formality, and the Limits of Managed Peace - Andriansyah, Yuli (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2026)
This editorial critically examines the Board of Peace as a proposed mechanism for Gaza’s stabilization and questions its capacity to deliver genuine peace and Palestinian independence. Rather than treating the Board as a neutral innovation in international governance, the editorial argues that it risks becoming a formal instrument for managing Palestinian dispossession without resolving its political causes. The analysis is based on a critical synthesis of recent academic literature on peacebuilding, post-conflict governance, international trusteeship, legitimacy, accountability, and Palestinian self-determination, combined with policy and media evidence available up to February 2026. The editorial finds that the Board of Peace suffers from four major weaknesses: fragile substantive legitimacy despite formal international endorsement; excessive concentration of authority in an externally led structure; limited Palestinian agency in decision-making; and an overemphasis on stabilization, reconstruction, and demilitarization without a credible path toward sovereignty. It further argues that reconstruction funding and technocratic administration may create the appearance of progress while postponing core issues such as occupation, borders, refugees, territorial unity, equal rights, and statehood. The Board’s possible marginalization of established multilateral mechanisms also raises concerns about accountability and the weakening of rights-based international governance. The editorial concludes that the Board of Peace is unlikely to fulfill Palestinian aspirations for peace and independence unless it is subordinated to self-determination, representative authority, territorial integrity, and enforceable political rights. Without these foundations, it remains a formal peace architecture rather than a pathway to emancipation.